Comparative analysis of the efficiency and ergonomics of wired and wireless ultrasound systems - A. A. Emel'yantsev; I. S. Zheleznyak; I. V. Kipriyanova; A. Ya. Latysheva; G. G. Romanov; L. V. Voronkov; T. D. Vengerovich (Вестник медицинского института «Реавиз»: Реабилитация, врач и здоровье)
The form factor of an ultrasound device with a wireless sensor has become firmly established in the standards for equipping medical institutions in recent years. In the Russian science literature there is a limited number of works on the practical application of such systems and a description of their advantages and disadvantages. It is important to evaluate the capabilities of a wireless ultrasound device in diagnosing urgent conditions.Purpose of the study: to compare the effectiveness, advantages and ease of use of wireless ultrasound diagnostic sensors in relation to stationary devices. A comparative analysis of the wireless ultrasonic sensor "Uprobe-C5PL" (Sonostar, China) with stationary devices "DC-70" (Mindray, China), "CX-50" (Philips, Netherlands), "Logic E9" (GE, USA). A total of 40 patients were studied. The comparison was carried out based on the following characteristics: comparison of measured organ sizes, identification of pathological conditions, consistency of results between several medical experts, ergonomic characteristics and ease of use.Results: there was no statistically significant differences (Mann– Whitney U test with Bonferroni correction, p > 0.05) and a strong correlation (r = 0.99; p < 0.01) between the measured values of organ sizes and pathological structures. The wireless sensor showed the highest diagnostic sensitivity – 91.7% and accuracy – 97.5% in detecting free fluid in the main cavities. A high agreement of results between expert was revealed (Kappa-Cohen coefficient, K = 0.836).Conclusion. The wireless ultra-sound sensor is not inferior to stationary devices in identifying free fluid and other pathological conditions within the framework of urgent studies. At the same time, the wireless form factor increases ease of use in confined spaces due to the mobility of the diagnostician and the autonomy of the device. When routinely examining a large number of patients, a wireless sensor is less convenient and informative than high-end devices.